2020
DOI: 10.1186/s12864-020-06933-z
|View full text |Cite
|
Sign up to set email alerts
|

Population analysis of the Korean native duck using whole-genome sequencing data

Abstract: Background: Advances in next-generation sequencing technologies have provided an opportunity to perform population-level comparative genomic analysis to discover unique genomic characteristics of domesticated animals. Duck is one of the most popular domesticated waterfowls, which is economically important as a source of meat, eggs, and feathers. The objective of this study is to perform population and functional analyses of Korean native duck, which has a distinct meat flavor and texture phenotype, using whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A total of 7,243,250 SNPs and 864,777 indels were identified in the Shan-ma duck genome in Table 1 . The number of SNPs and indels in the Shan-ma duck detected in this study were less than other duck types 15 , 16 , because the trial birds were full sibling individuals of one breed. In this study, the number of SNPs in intergenic, intronic and exonic regions including exonic stop gain, exonic stop loss, exonic synonymous, and exonic non-synonymous were 3,531,432 (52.21%), 3,232,152 (47.79%) and 114,824 (1.70%), respectively.…”
Section: Resultsmentioning
confidence: 53%
“…A total of 7,243,250 SNPs and 864,777 indels were identified in the Shan-ma duck genome in Table 1 . The number of SNPs and indels in the Shan-ma duck detected in this study were less than other duck types 15 , 16 , because the trial birds were full sibling individuals of one breed. In this study, the number of SNPs in intergenic, intronic and exonic regions including exonic stop gain, exonic stop loss, exonic synonymous, and exonic non-synonymous were 3,531,432 (52.21%), 3,232,152 (47.79%) and 114,824 (1.70%), respectively.…”
Section: Resultsmentioning
confidence: 53%
“…This study examined positive selection by scanning both single locus and genomic blocks to obtain comprehensive and reliable genes with selection signatures. VCFtools ( Danecek et al., 2011 ) was used to calculate population Fst statistic as previously described between different populations ( Cagan and Blass, 2016 ; Lee et al., 2020 ; Wang et al., 2021a ) and the per-site Fst value was calculated between two populations with the parameter “–weir-fst-pop”. The R packages “GeneNet” ( Schaefer et al., 2015 ) was implemented to get the Z-transform Fst value for visualization in Manhattan plots by the R package “CMplot” in Figure 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the maturity of sequencing technologies, diverse genomic studies have been performed to identify genomic loci affecting meat quality in pigs. Especially, several population-level studies using short read data, such as population genomic analyses [ 5 7 ] and genome-wide association studies [ 8 10 ], have identified plentiful regions and genes associated with the traits at the whole-genome level.…”
Section: Introductionmentioning
confidence: 99%